1972
DOI: 10.3168/jds.s0022-0302(72)85457-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Aspects of Udder Infections

Abstract: Information on the presence or absence of bacterial infections and abnormal secretions in each quarter of cows in their initial survey on the New York State Veterinary College Mastitis Program was used to obtain several criteria of udder infection. Year-season and stage of lactation effects were statistically significant for several criteria of infection in first, second, and later lactation groups but did not explain much of the variation in any infection criterion. Age within first and second lactation group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

1978
1978
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(10 citation statements)
references
References 11 publications
1
8
1
Order By: Relevance
“…Table 5 gives estimates of means for parities 1 through 3. Means for the clinical mastitis traits agree with (13,18,22,23) indicating lower frequency in first lactations. For example, SUM increased from 2.48 in first lactation to 5.16 in second.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Table 5 gives estimates of means for parities 1 through 3. Means for the clinical mastitis traits agree with (13,18,22,23) indicating lower frequency in first lactations. For example, SUM increased from 2.48 in first lactation to 5.16 in second.…”
Section: Resultssupporting
confidence: 66%
“…O'Bleness et al (15) reported a genetic correlation of .44 between milk yield and incidence of clinical mastitis. Wilton et al (23) reported genetic correlations between milk yield in first lactation and mastitis incidence in later lactation that averaged around .30.…”
Section: Introductionmentioning
confidence: 99%
“…(2) and Wilton c.s. (12) do not confirm such statements. The present study, also provides evidence of an opposite tendency: more favourable figures with higher production and easier milking ( Table 4).…”
Section: Discussioncontrasting
confidence: 36%
“…Some assessments of the heritability of mastitis susceptibility suggest that progress for breeding more resistant cows is possible(i07, ill). Other researchers have produced low estimates of heritability (233). Part of the discrepancy relates to the difficulty of assessing mastitis susceptibility.…”
Section: Effects Of Mastitis Monitoring Systems On Awareness and Controlmentioning
confidence: 99%